TAMING THE ORIENTAL BAZAAR - Sohoni, Pushkar. ([S.l.])
1 online resource
Keywords: Taming the Oriental Bazaar examines the public market-hall as a key architectural feature of colonial South Asia. Representing a transition in the architectural programme, these buildings were meant to be monuments and markers of modernity in South Asia. The book: Explores how market-halls became an essential feature of colonial settlements from the mid-nineteenth through the mid-twentieth centuries Discusses public health policies and legislations central to the concerns of market-hall sanitation Reviews the elements of modernity, including institutions and systems established in the nineteenth century as India went from Company to Crown Studies the specific circumstances and histories of market halls in the towns and cities of Bengaluru, Vadodara, Mumbai, Kolkata, Hyderabad, Karachi, Lahore, Chennai, Pune, and others A key text in the study of colonial architecture, this book will be of interest to students, researchers as well as general readers of architecture, colonialism, history of architecture, history of medicine, public health, urbanism, and South Asian studies.